2019
DOI: 10.1507/endocrj.ej18-0579
|View full text |Cite
|
Sign up to set email alerts
|

Risk and protective factors of co-morbid depression in patients with type 2 diabetes mellitus: a meta analysis

Abstract: The aim from this paper is to identify the main influencing factors of co-morbid depression among T2DM (Type 2 Diabetes Mellitus) patients and to provide reliable evidence for relative researches. A systematic review and meta-analysis of risk factors for co-morbid depression in T2DM was performed on all retrieved studies through an observational research of network database. Data were analyzed by Review Manager 5.3 from the extracted results, the heterogeneity index of the studies was determined using Chi-squa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 35 publications
1
12
0
4
Order By: Relevance
“…15% and 6.1% respectively (Brandão & Cardoso, 2018). Regular exercise poses as a protective factor in patients with coexisting diabetes and depression (Simayi & Mohemaiti, 2019), and is associated with enhanced QoL (Jing et al., 2018). Furthermore, vigorous rather than moderate physical activity is revealed to serve as a vigilant element against diabetes, obesity, and hypertension (Dumith et al., 2019).…”
Section: Possible Intervention Management and Treatment Strategiesmentioning
confidence: 99%
“…15% and 6.1% respectively (Brandão & Cardoso, 2018). Regular exercise poses as a protective factor in patients with coexisting diabetes and depression (Simayi & Mohemaiti, 2019), and is associated with enhanced QoL (Jing et al., 2018). Furthermore, vigorous rather than moderate physical activity is revealed to serve as a vigilant element against diabetes, obesity, and hypertension (Dumith et al., 2019).…”
Section: Possible Intervention Management and Treatment Strategiesmentioning
confidence: 99%
“…Several clinical and psychosocial factors have been reported to be associated with poor treatment response in patients with MDD, including poor treatment adherence, physical and psychiatric comorbidities, bipolarity, and high level of neuroticism [ 6 , 12 14 ]. Physical comorbidities, including diabetes [ 15 , 16 ], heart diseases [ 17 ], functional gastrointestinal disorders (FGIDs) [ 18 ], thyroid disease [ 19 ], systemic lupus erythematosus (SLE) [ 20 ], and rheumatoid arthritis [ 21 ], have been implicated in the development and prognosis of common mental disorders, especially mood disorders. In addition, a group of anxiety disorders (including panic disorder, generalized anxiety disorder, social anxiety disorder, and obsessive-compulsive disorder), attention deficit hyperactivity disorder (ADHD), substance use disorders (SUDs), and personality disorders were found to be more prevalent in patients with MDD [ 22 25 ], or predictive of worse outcomes or slower remission [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, in this study, female sex and inferior education's association with depressive symptoms were significant in the univariate analyses. Although, the literature reviews investigating the association between depression and diabetes have shown these as risk factors for depression [18,41] Regarding health-related behavioral factors, fair and poor subjective health conditions and high perceived stress were significantly associated with depressive symptoms. In particular, poor subjective health conditions and high perceived stress significantly increased the risk of depressive symptoms.…”
Section: Discussionmentioning
confidence: 98%
“…A large population-based study demonstrated that comorbidity and physical impairment were correlated with depression in people with diabetes [17]. Additionally, a meta-analysis of 14 cross-sectional studies reported that female sex, insulin use, diabetes complications, low educational level, physical inactivity, living alone, and unemployment were significant risk factors for depressive symptoms in people with diabetes [18]. A community-based epidemiological study investigating 3540 Korean adults with type 2 diabetes in a city identified low income, unemployment, current smoking, use of oral hypoglycemic medications or insulin, and physical inactivity as significant factors associated with depressive symptoms [19].…”
Section: Introductionmentioning
confidence: 99%